Dental Health Education for Managing Poor Oral Hygiene in Middle-Aged Female Patient - Yudha Rahina; Ni Putu Dila Wahyuni; Ni Kadek Ari Astuti; Ketut Virtika Ayu; Dewa Made Wedagama; Pudak Elang (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Background: Oral health has not received sufficient attention from society. Oral hygiene is often neglected, and proper toothbrushing has not yet become a habit. This case study aimed to provide dental health education to middle-aged patients to improve their oral health status. Case: A 57-year-old female patient complains of painful mouth sores on the lower lips, easily bleeding gums, and unpleasant breath. The patient had poor oral hygiene. Case Treatment: The recurrent minor aphthous stomatitis, can be treated with Triamcinolone acetonide 0.1%. The condition of easily bleeding gums and bad breath are managed by performing scaling and root planning on the patient. However, this patient needs to be educated to maintain her oral health. Discussion: Providing dental health education is a crucial aspect to offer patients, alongside addressing their dental concerns. Dental health education was delivered using direct persuasive communication techniques on days 1, 7, and 14, coinciding with treatment and follow-up appointments. Conclusion: The chief complaint of the patient and several other complaints have been addressed successfully. Dental health education for middle-aged patients has proven effective in addressing poor oral hygiene conditions.